2017
DOI: 10.1016/j.bbadis.2016.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Reelin expression is up-regulated in mice colon in response to acute colitis and provides resistance against colitis

Abstract: Reelin is an extracellular matrix protein first known for its key role in neuronal migration. Studies in rodent small intestine suggested that reelin protects the organism from intestinal pathology. Here we determined in mice colon, by real time-PCR and immunological assays, the expression of the reelin signalling system; its response to dextran sulphate sodium (DSS) and the response of wild-type and reeler mice to DSS-treatment. DNA methylation was determined by bisulfite modification and sequencing of genomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Nevertheless, a relation between high expression of reelin and hypomethylation of the RELN promoter region in myeloma cell lines as well as in patients with cancer has been reported (60). Similarly, up-regulation of reelin expression in mouse colon in response to acute colitis has been associated with a decrease in DNMT1 and in RELN promoter methylation (61).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a relation between high expression of reelin and hypomethylation of the RELN promoter region in myeloma cell lines as well as in patients with cancer has been reported (60). Similarly, up-regulation of reelin expression in mouse colon in response to acute colitis has been associated with a decrease in DNMT1 and in RELN promoter methylation (61).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 A few studies have reported dysfunction of CASK with esophageal carcinoma and colitis. 2,3 This patient presented with refractory constipation with abdominal distension at onset, followed by neurological manifestations and displayed HD and PCH with CASK mutation. The CASK loss-of-function mutation led to the decreased expression of protein 4.1, which affected microfilament contraction and cell differentiation, leading to cytoskeletal abnormalities in the axons of the ganglion cells in the distal bowel and central nervous system; smooth muscle dysfunction, further contributed to these presentations.…”
Section: Discussionmentioning
confidence: 99%
“…Although Hirschsprung’s disease (HD) is the most common congenital malformation of the enteric nervous system in children, its genetic etiology remains unclear. 1 Calcium/calmodulin-dependent serine protein kinase (CASK) is associated with digestive diseases, including cancer and proctitis; 2 , 3 however, CASK mutations have not been shown to cause HD. We report a case involving a male child with CASK mutation and HD, demonstrating the disease’s typical neurological manifestations.…”
Section: Introductionmentioning
confidence: 99%
“…Following sacrifice, the colon was removed, washed with ice‐cold saline solution and fixed by overnight incubation with phosphate buffer saline (PBS; in mM, 137 NaCl, 2.7 KCl, 10 Na 2 HPO 4 , and 1.8 KH 2 PO 4 ; pH7.4) containing 4% paraformaldehyde for histological analysis. The progression of the colon inflammation was assessed by determining disease activity index (DAI), histological score and by the messenger RNA levels of the proinflammatory cytokines IL‐1β and TNF‐α, as described (Carvajal et al, 2017). For DAI evaluation, daily, throughout the DSS‐treatment, animals were monitored for weight loss, stool consistency and blood in the feces (scale of 0–3).…”
Section: Methodsmentioning
confidence: 99%